The Role of Parents in Children's Christian Faith Education Through the Tandak Timang Tradition in Batu Badinding Village - Silipta Silipta; Lidia Selfitri (Harati: Jurnal Pendidikan Kristen, 2025)
The Tandak Timang tradition is an oral cultural heritage of the Dayak Ngaju community which contains moral, spiritual, and character education values that are relevant to the development of Christian children's faith. This study aims to describe the role of parents in children's Christian faith education through the tradition of Tandak Timang in Batu Badinging Village. The research approach used is qualitative descriptive with interview, observation, and documentation techniques. The results of the study show that parents play an important role as heirs of cultural values, interpreters of spiritual meaning, exemplars of faith, and preservers of traditions that are loaded with the values of love, loyalty, responsibility, and respect for ancestors. Through the active involvement of parents, Tandak Timang functions not only as a cultural expression, but also as an effective means of forming children's character and spirituality in the light of Christian teachings. Thus, the integration between faith and culture through the role of parents strengthens the identity of Dayak Ngaju faith and culture in the midst of modernity.